2014
DOI: 10.1038/ncomms4518
|View full text |Cite
|
Sign up to set email alerts
|

Frequent mutations in chromatin-remodelling genes in pulmonary carcinoids

Abstract: Pulmonary carcinoids are rare neuroendocrine tumors of the lung. The molecular alterations underlying the pathogenesis of these tumors have not been systematically studied so far. Here we perform gene copy number analysis (n=54), genome/exome (n=44) and transcriptome (n=69) sequencing of pulmonary carcinoids and observe frequent mutations in chromatin-remodeling genes. Covalent histone modifiers and subunits of the SWI/SNF complex are mutated in 40% and 22.2% of the cases respectively, with MEN1, PSIP1 and ARI… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

17
265
1
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 262 publications
(284 citation statements)
references
References 35 publications
(54 reference statements)
17
265
1
1
Order By: Relevance
“…The high prevalence of mutations in chromatin remodelling genes suggests that these mutations are crucial to drive tumorigenesis in a precisely defined spectrum of required cellular pathways (Fernandez-Cuesta et al 2014). Previous studies already reported impairment in specific histone 4 modification levels.…”
Section: Pulmonary Netmentioning
confidence: 99%
See 2 more Smart Citations
“…The high prevalence of mutations in chromatin remodelling genes suggests that these mutations are crucial to drive tumorigenesis in a precisely defined spectrum of required cellular pathways (Fernandez-Cuesta et al 2014). Previous studies already reported impairment in specific histone 4 modification levels.…”
Section: Pulmonary Netmentioning
confidence: 99%
“…Mutations of PTEN were found in 7.3% of PanNET and more recently mutations in TSC2, 8.8%; PIK3CA, 1.4% were also described (Perren et al 2000. TP53 mutations are rare in PanNET Jiao et al 2011, Cao et al 2013, Francis et al 2013, Cancer Genome Atlas Research 2014, Fernandez-Cuesta et al 2014, Cromer et al 2015, Lichtenauer et al 2015, Witkiewicz et al 2015, Scarpa et al 2017.…”
Section: Cellmentioning
confidence: 99%
See 1 more Smart Citation
“…Epigenetic dysregulation is known to play a key role in other NET development, including tumors of pancreatic and bronchial origin (8,9). Integrated molecular profiling based on methylation analysis has recently been shown to identify clinically distinct subgroups of lung carcinomas, including a neuroendocrine-specific "epitype" (10).…”
Section: Introductionmentioning
confidence: 99%
“…The libraries were then sequenced with a 2 Â 100 bp paired-end protocol to a minimum mean coverage of 30Â. Data were processed and analyzed as described previously (16,17). All data have been deposited at the European Genome-phenome Archive under the accession code EGAS00001002491.…”
Section: Viability Assays and Compound Activity Predictionmentioning
confidence: 99%